Some Changes in Chemical Properties on Ultisol Soil Giving Due Some of Organic Fertilizer and The Incubation Period - Armada Karokaro; Alida Lubis; Fauzi jamal (Jurnal Agroekoteknologi, 2017)
This research was conducted in the room of Laboratory, Agriculture Faculty , University of North Sumatera, Medan and soil analize in Analitical Laboratory of PT. Socfindo Medan in Maret-Juni 2016. This research used Completly Randomized Factorial Design, with 2 factors. The first factor is organic fertilizer consist of without organic fertilizers (P0), compost of Tithonia (P1), compost of durian’s shell (P2), compost of palm oil fruit bunches waste (P3), chicken manure (P4), compost of Tithonia + chicken manure (P5), compost of durian’s shell + chicken manure (P6), compost of palm oil fruit bunches waste + chicken manure (P7). The second factor is incubation period (I) are one week and two weeks. The result showed that application of organic fertilizer are compost of Tithonia, compost of durian’s shell, compost of palm oil fruit bunches waste, chicken manure, and the mixed compost with chicken manure was significant for  C-Organic, totally soil-N, totally soil-P, and K exchange soil in Ultisol. The period incubation was not significant for C-Organik, totally soil-N, totally soil-P, and  K exchange. The interaction of organic fertilizer application and period of incubation treatments was not significant for all parametric